Using 3.0 eV Large Bandgap Conjugated Polymer as Host Donor to Construct Ternary Semi‐Transparent Polymer Solar Cells: Increased Average Visible Transmittance and Modified Color Temperature. Issue 22 (21st April 2022) - Liu, Xuanchen; Liu, Zhitian; Chen, Mingqing; Wang, Qian; Pan, Feilong; Liu, Haizhen; Zhang, Lianjie; Chen, Junwu
Abstract: Although optical engineering strategy has been utilized to optimize average visible transmittance (AVT) of semi‐transparent organic solar cells (ST‐OSCs), judicious selection of active layer materials should be more direct and basic. Herein, an efficient ternary active layer is constructed with a wide bandgap (3.0 eV) fluorescent polymer FC‐S1 as host donor, a middle bandgap polymer PM6 as guest donor, and a narrow bandgap non‐fullerene Y6‐BO as acceptor. Using FC‐S1 as the host donor can allow more visible photons to penetrate the device. In the absence of optical engineering, the ternary ST‐OSC with FC‐S1:PM6:Y6‐BO = 1:0.3:1.5 active layer of 30 nm thickness displays a much higher AVT of 49.28% than that of 32.34% for a PM6:Y6‐BO = 1.3:1.5 based binary ST‐OSC. The ternary ST‐OSC provides a good power conversion efficiency of 6.01%, only slightly lower than 7.15% for the binary ST‐OSC. The ternary ST‐OSC also demonstrates a color rendering index (CRI) of 87 and a correlated color temperature (CCT) of 6916 K, all better than CRI of 80 and CCT of 9022 K for the binary ST‐OSC. Moreover, the backbone of FC‐S1 is mainly composed by fluorene and carbazole, two easily‐accessible aromatic rings, which would meet low‐cost concern of ST‐OSCs. Abstract : A wide bandgap (3.0 eV) fluorescent polymer FC‐S1 is used as host donor to realize high‐performance ternary active layer. Relative to middle bandgap polymer and narrow bandgap non‐fullerene PM6:Y6‐BO binary system, the semi‐transparent device based on a 30 nm thick FC‐S1:PM6:Y6‐BO ternary active layer achieves largely enhanced visible‐light transmittance and light utilization efficiency as well as better color rendering index and correlated color temperature.